2015
DOI: 10.1177/1103308815569391
|View full text |Cite
|
Sign up to set email alerts
|

Media Consumption and the Identity Projects of the Young

Abstract: The purpose of this research is to discern the different roles of media in the identity projects of the young. Building on the idea of social identification, the analysis is focused on defining the different ways and criteria in which their own media consumption is accounted for by the young when making sense of themselves and others. Empirical data for the study included 53 Finnish university students’ essays on their relationships with different media vehicles and contents. The findings indicate that media c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Young people use media for viewing images of people's lives both similar to and different from their own. This can be interpreted as escapism, but can also be understood as a means of identity formation (Cranmer, 2010;Lim et al, 2013;Oksama and Turtiainen, 2004;Sihvonen, 2015).…”
Section: Ict Use Among Vulnerable and Marginalized Young Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Young people use media for viewing images of people's lives both similar to and different from their own. This can be interpreted as escapism, but can also be understood as a means of identity formation (Cranmer, 2010;Lim et al, 2013;Oksama and Turtiainen, 2004;Sihvonen, 2015).…”
Section: Ict Use Among Vulnerable and Marginalized Young Peoplementioning
confidence: 99%
“…The young people who preferred calling or talking to people face-to-face were also the ones who stated that they felt insecure with their ICT skills. A lack of appropriate education (Van Deursen et al, 2011, 2015 and/or general illiteracy (Cranmer, 2010) may provide an explanation for this, as ICT and social media are still mostly based on communication through text which is challenging for those who have difficulty in reading and writing.…”
Section: Integration and Social Interactionmentioning
confidence: 99%
“…Our qualitative findings showed that Black adolescents" attitudes and perceptions are particularly pliable with their immersion in social media. Social media, which first emerged in the 2000s, has the power to affect social change in society and has cemented itself as an indispensable mode of communication among today's youth (Sihvonen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, “like” buttons can be clicked back and forth on Instagram, and Snapchat provides its users with a streak score that reflects the number of consecutive days when two users have sent messages to each other (Griffiths, 2018). To understand social media platforms’ role from the adolescents’ perspective, the online sphere has to be seen as a central social context for adolescents, where they, for instance, construct their identities (Hübner Barcelos and Vargas Rossi, 2014; Sihvonen, 2015), cultivate their social relationships (Décieux et al , 2019; Hübner Barcelos and Vargas Rossi, 2014; Thulin, 2018), take political action (Allaste and Saari, 2020) and learn about the events happening around the world (Bergström and Jervelycke Belfrage, 2018). In some studies, the high (or even extensive) usage of social media has also been connected with the so-called “fear of missing out”, which refers to the desire to keep up with all the things happening within one’s social sphere (Handa and Ahuja, 2020; Sultan, 2021).…”
Section: Adolescents and Unhealthy Food Marketing In Social Mediamentioning
confidence: 99%